Literature Study of The Implementation and Policy of Military Telemedicine In Support Of Troop Mobilization In Conflict Areas - Desi Tirtawati; Sutanto Sutanto; Guntur Eko Saputro (UNIVERSITAS PAKUAN, 2026)
Abstract The advancement of information technology has revolutionized military healthcare through telemedicine, particularly in supporting troop mobilization in conflict zones. However, the urgency of remote medical services in high-risk areas often conflicts with legality and information security challenges. This study aims to analyze the legal framework and regulatory challenges in implementing telemedicine within military operations. Using a literature review method, this research systematically reviews 25 national and international journal articles. The analysis focuses on legal voids, infrastructure policies, and legal protection of medical data security in cyber transmission. The findings indicate that while military telemedicine effectively enhances operational readiness and specialist access, its implementation is hindered by the lack of specific legal frameworks and vulnerabilities in protecting soldiers' personal data in the field. Therefore, harmonization of defense and health policies, along with the establishment of adaptive regulations, is required to ensure legal certainty and cyber security in military telemedicine administration. Keywords: Military Telemedicine, Health Regulation, Data Protection, Cyber Law, Conflict Zone.